Distinct Trajectories of Fatigue Among Families with Post-Intensive Care Syndrome - Chen Q; Huang Y; Xu L; Chen X (International Journal of General Medicine, 2025)
Qiong Chen,1,* Yanjin Huang,2,* Limin Xu,1 Xiaomei Chen3 1Department of Intensive Care Medicine, Xiamen Haicang Hospital, Xiamen, Fujian, People’s Republic of China; 2Department of Nursing, Xiamen Haicang Hospital, Xiamen, Fujian, People’s Republic of China; 3Department of Pain, Xiamen Haicang Hospital, Xiamen, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiong Chen, Department of Intensive Care Medicine, Xiamen Haicang Hospital, No. 89 haiyu Road, Haicang District, Xiamen, Fujian, 361026, People’s Republic of China, Tel +86 177 50612461, Email chenqiongfff@163.comPurpose: This study investigated the trajectories of fatigue symptoms in post-intensive care syndrome among family members (PICS-F) and aimed to explore the sociodemographic and clinical factors related to these trajectories.Patients and Methods: This was a longitudinal observational study conducted in an intensive care unit (ICU) of a tertiary hospital in Xiamen, China. Data were collected when adult patients were transferred from the ICU to the ordinary ward of the hospital or discharged, and at 1 month, 2 months, and 3 months later. Fatigue symptoms were assessed using the Fatigue Severity subscale, and sociodemographic and clinical information was collected. The study used latent growth mixture modelling to construct the trajectories of fatigue symptoms, and logistic regression was used to identify the factors associated with fatigue.Results: A total of 133 family members with PICS-F were included. Four trajectories of fatigue symptoms were identified and attributed to two groups. Controlling for individual’s age and severity of illness, the length of stay in the ICU and in the hospital increased the odds of belonging to the fatigue group, whereas a lower level of dependence (higher Barthel index score) was a protective factor for the non-fatigue group.Conclusion: Four distinct trajectories of fatigue symptoms were identified. Longer ICU stays and hospitalization durations of patients may increase the risk of fatigue of PICS-F, while a lower level of dependence has the potential to reduce the risk of fatigue. Further multicenter studies with larger sample sizes and diverse populations are needed to validate this hypothesis.Keywords: fatigue, latent growth mixture modelling, longitudinal study, post-intensive care syndrome-family